2014
DOI: 10.1007/978-3-319-08596-8_77
|View full text |Cite
|
Sign up to set email alerts
|

Gamification for Low-Literates: Findings on Motivation, User Experience, and Study Design

Abstract: This study investigated the effects of the gamification elements of scaffolding, score and hints on the user enjoyment and motivation of people of low literacy. In a four-condition within-subjects experiment, participants performed mental spatial ability tests with the aforementioned elements. Quantitative results were inconclusive, but post-test interviews provided insights on the limited effectiveness of the gamification elements. Complex questionnaire wording, high task difficulty, and an improperly situate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The concept of player experience is complex, covering multiple dimensions of interaction, including positive affect, negative affect, flow, sensory immersion, tension, challenge, and competence (Gajadhar, Kort, & IJsselsteijn, 2008;IJsselsteijn, de Kort, Poels, Jurgelionis, & Bellotti, 2007;Schouten, Pfab, Cremers, van Dijk, & Neerincx, 2014). Some of these dimensions are positive or neutral while others are negative.…”
Section: Player Experiencesmentioning
confidence: 97%
“…The concept of player experience is complex, covering multiple dimensions of interaction, including positive affect, negative affect, flow, sensory immersion, tension, challenge, and competence (Gajadhar, Kort, & IJsselsteijn, 2008;IJsselsteijn, de Kort, Poels, Jurgelionis, & Bellotti, 2007;Schouten, Pfab, Cremers, van Dijk, & Neerincx, 2014). Some of these dimensions are positive or neutral while others are negative.…”
Section: Player Experiencesmentioning
confidence: 97%
“…We also looked into whether and how the GEQ was modified in the studies. Some included only a subset of the GEQ components or even a subset of items of a specific component, with the reported number of items ranging from 5 (e.g., only the Flow component with 5 items [32]) to 25 items (i.e., 5 subcomponents each with 5 items [63]). However, justification for the selection was seldom provided.…”
Section: Application Of the Geqmentioning
confidence: 99%
“…Other oddities include: (i) mis-citing another questionnaire with the same acronym "Game Engagement Questionnaire" [4,5]; (ii) citing the KidsGEQ [44], a poster containing only seven example items, for a study with university students; (iii) citing the Future Play [41] and Fun & Games [10] which do not include any GEQ items; (iv) citing the Social Presence in Gaming Questionnaire (SPGQ) of which items are different from the core GEQ [43,60]; (v) citing the URL of the homepage of the research lab of which the GEQ originators were members, but without specifying the location of the document [63]; (vi) providing the authors and title of the GEQ without publication year or status [21]. These add up to 8 instances (or more than 10%) of the reviewed papers.…”
Section: Confusing and Untraceable Referencesmentioning
confidence: 99%
“…It is seen that voluntary participants (n = 21), customers (n = 5), writers and players (n = 4), patients (n = 4) and civil cervants (n = 4) constitute the research samples of the studies as well. Schouten et al examined the users' experiences and motivations toward gamification among individuals with low levels of literacy [62]. This study showed that individuals with low educational level are also included in the studies on gamification approach as participants.…”
Section: Distribution Of the Studies Based On Research Samplementioning
confidence: 99%